2010
DOI: 10.1038/icb.2010.44
|View full text |Cite
|
Sign up to set email alerts
|

5‐aminoimidazole‐4‐carboxamide ribonucleoside and AMP‐activated protein kinase inhibit signalling through NF‐κB

Abstract: Activation of nuclear factor‐kappa B (NF‐κB) is one of the most important pro‐inflammatory mechanisms in disease. In this study, we show that 5‐aminoimidazole‐4‐carboxamide ribonucleoside (AICAR), an intermediate in nucleoside metabolism, inhibits signalling by NF‐κB in three cell types, including bovine aortic endothelial cells (BAEC). The block in the NF‐κB signalling pathway occurred beyond degradation of IκB‐α and movement of p65 into the nucleus of BAEC. There was, however, reduced binding of NF‐κB from A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
37
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 40 publications
4
37
1
Order By: Relevance
“…Endothelial cells also express both ␣ subunits of AMPK, and conflicting reports of their roles have also emerged (40). Consistent with our observations in osteoclast progenitor cells, overexpression of AMPK␣1 or AMPK activation by AICAR also reduces NFB signaling in aortic endothelial cells (41). A similar study in endothelial cells demonstrated that AMPK attenuates NFB activation via direct phosphorylation of IKK␤ on Ser-177 and Ser-181 by AMPK␣2 but not AMPK␣1 (40).…”
Section: Discussionsupporting
confidence: 79%
“…Endothelial cells also express both ␣ subunits of AMPK, and conflicting reports of their roles have also emerged (40). Consistent with our observations in osteoclast progenitor cells, overexpression of AMPK␣1 or AMPK activation by AICAR also reduces NFB signaling in aortic endothelial cells (41). A similar study in endothelial cells demonstrated that AMPK attenuates NFB activation via direct phosphorylation of IKK␤ on Ser-177 and Ser-181 by AMPK␣2 but not AMPK␣1 (40).…”
Section: Discussionsupporting
confidence: 79%
“…MTX is known to inhibit aminoimidazole carboxamide ribonucleotide (AICAR) transformylase, which results in accumulation of AICAR that further sensitizes AMP-activated protein kinase (AMPK) 11 . AMPK has been shown to induce NAMPT transcription in glucose-restricted skeletal myoblasts, which may appear to contradict our findings here; however, AICAR (through activation of AMPK) has also been shown to inhibit nuclear factor-κB (NF-κB) 12,13 . NF-κB has been shown to induce NAMPT activity, thus inhibition of this important proinflammatory transcription factor in MTX-treated patients may contribute to lower NAMPT concentrations in these patients.…”
Section: Rheumatologycontrasting
confidence: 56%
“…Furthermore, the pathway(s) involved in AMPK-induced suppression of inflammation and insulin sensitivity remains yet to be elucidated. Recent studies show AICAR and phenformin inhibits LPS-induced NF-κB signalling and also the transcription of NF-κB-dependent genes [15]. NF-κB is a transcription factor that regulates the expression of pro-inflammatory mediators and has been described to play an important role in the pathogenesis of diabetes and its associated complications [23].…”
Section: Discussionmentioning
confidence: 99%